Indicators of teenage career readiness An analysis of longitudinal data from eight countries - Covacevich, Catalina (OECD Education Working Papers, 2021)
The aim of the OECD Career Readiness project is to identify patterns of teenage attitudes and activities that are associated with better transitions into employment by analysing multiple national longitudinal datasets. This paper looks for further evidence of the link between teenage activities, experiences and career-related thinking and adult career outcomes by analysing 10 new datasets from eight countries. Overall, the results of this paper find further evidence that secondary school students who explore, experience and think about their futures in work frequently encounter lower levels of unemployment, receive higher wages and are happier in their careers as adults. The findings of this paper are analysed together with the evidence from the two previous working papers of the Career Readiness project, concluding that there is international evidence to support 11 out of the 14 potential indicators that were explored as indicators of career readiness